Pengaruh Persistensi Laba, Ukuran Perusahaan Dan Alokasi Pajak Terhadap Pearnings Quality - Rosiana Ramadhon; Ika Listyawati; Alfin Muslikhun (Jurnal Kendali Akuntansi, 2023)
The purpose of this study is to examine and analyze empirically Influence Persistence of Earnings (X1), Company Size (X2), Allocation Tax (X3) on the Earnings Quality (Y) in manufacturing companies listing on the Stock Exchange. This type of research is classified as research that is causative. The population of this research is manufacturing companies listed in Indonesia Stock Exchange (BEI) in 2019 until 2021. The sample was determined by purposive sampling method, to obtain a sample of 10 manufacturing companies. The data used in this research is secondary data. Data collected by using documentation obtained through the official website IDX: www.idx.co.id and obtained from the website: www.yahoofinace.com. Analysis of the data used is multiple regression analysis. The data obtained were then processed using descriptive statistics test, classic assumption test (Normality Test, Test Multicolinearity, Hesteroskedastisitas Test), Regression Test, Test The coefficient of determination, hypothesis test (F-test, t test) were analyzed with SPSS software elp.